Knowledge, attitude and practice regarding sexual and reproductive health rights among married adolescents in urban slums of Bangladesh: A cross-sectional survey - Topa, Adity Roy; Shiblee, Shafayatul Islam; Rashid, Md. Harunor (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Adolescents, especially married adolescents living within urban slum communities, encounter significant difficulties in obtaining and exercising their sexual and reproductive health rights (SRHR). This study aimed to determine the knowledge, attitude, and practice of SRHR and its associated factors among married adolescents living in urban slums. Methods: A cross-sectional survey of 500 married adolescent girls living in slums in Dhaka and Gazipur, Bangladesh, was conducted in the icddr,b Health and Demography Surveillance System areas. We interviewed them using a pretested questionnaire to assess their knowledge, attitude, and practice of SRHR. Data on their sociodemographic variables, such as household asset items and age and education, were collected. Principal component analysis was used to create wealth indices. Results: Knowledge of self-care during menstruation and the oral contraceptive pill was almost universal, though knowledge of condoms, abortion, danger signs of pregnancy and sexually transmitted infections was low. They (70%) agreed that young people should have access to menstruation-related hygiene facilities, contraception and sex education, though there was less agreement regarding abortion being a woman’s right. The use of antenatal care and institutional-level delivery was also low. Age, years of schooling and prior pregnancy were positively associated with their knowledge levels. Important attitudinal and practice variations were noted between regions, Gazipur being the most disadvantaged. Conclusion: There are important gaps in knowledge and practice in SRH service-seeking in this slum population. Heterogeneity in the slum population must be recognised to design services that reach the most disadvantaged group.